The expressions for (h+g)(x) and (h-g)(x) and evaluate (h-g) (4) is 9x-3 , x+3 and 7
A function is defined as the law that build relation between a dependent variable and an independent variable.
It is given that
functions g and h are defined for all real numbers x as follows.
g(x) = 5x
h(x) = 4x-3
the expressions for (h+g)(x)= ?
(h+g)(x)= 5x+4x-3
(h+g)(x)= 9x-3
and (h-g)(x) = ?
(h-g)(x) = 5x - 4x +3
(h-g)(x) = x+3
and evaluate (h-g) (4).
(h-g)(x) = x+3
at x = 4
(h-g)(4) = 4+3 = 7
Therefore the value for the functions have been determined.
To know more about Function
https://brainly.com/question/12431044
#SPJ1